Kimura's Disease Finding on Ocular Adnexal Mass - Tiendie, Nonidha; Fatmariyanti, Susy; Ridholia, Ridholia (Universitas Airlangga, 2024)
Introduction: Kimura's disease is an unknown chronic lymphoproliferative inflammatory disease affecting the skin, soft tissues, and lymph nodes. Until September 2020, only 200 cases of Kimura's disease were reported worldwide, however, their exact incidence is unknown. Here, we are interested in reporting a patient with Kimura's disease of the ocular adnexa due to its rarity and to enhance the knowledge of ophthalmologists about confirming the diagnosis of Kimura's disease. Case Presentation: A 40-year-old female presented with a chief complaint of a mass on her left nasal orbit for the last year. The mass gradually increased for six months, and it was painless. The systemic laboratory workup revealed eosinophilia and increased serum IgE. Contrast CT-Scan revealed a benign tumor, suspect dermoid cyst. She underwent surgery, and the histopathologic showed Kimura's disease. The patient was followed up on a scheduled basis, and there was no recurrence during four months of monitoring. Conclusions: A clinical, systemic laboratory, and histopathological examination is required to confirm the diagnosis of Kimura's ocular adnexa disease and determine the best therapy for the patient due to the high recurrence rate. Combining surgical excision with postoperative radiation is recommended as the most effective treatment in terms of controlling the residual lesion and minimizing the recurrence rate while causing the fewest side effects. Eosinophil screening regularly is advised to evaluate the recurrence rate.